Psychological Distress and Coping among Pregnant Women during the COVID 19 Pandemic - Rimal, Surya Prasad; Thapa, Kriti; Shrestha, Ramesh (Journal of Nepal Health Research Council, 2022)
Background: Mental health of pregnant individuals has been profoundly affected by the COVID-19 pandemic. Effective coping strategies are found to be associated with better psychological wellbeing during the COVID-19 pandemic. The objective of the present study is to assess psychological distress and coping among pregnant women during the COVID-19 pandemic. Methods: A descriptive cross sectional study was conducted from May 2020 to July 2020 among 115 pregnant women attending obstetric unit of a tertiary care centre using convenience sampling technique. Ethical approval was obtained from the Institutional Review Committee of the Institute. Covid-19 Peritraumatic Distress Index and Brief COPE inventory was used to collect the data. Data entry was done in Microsoft Office Excel 2007 and analysed in SPSS version 16. Results: Psychological distress was found in 2.6% of the participants. Psychological distress was significantly associated with occupation, fear of ANC visit, fear of visit to hospital for other health problems and fear of being alone or without help around delivery. Emotion focused coping was the most commonly used coping strategies among the pregnant women with the mean score of 21.37±3.130. Psychological distress and over all coping strategies had a positive correlation (<0.001). Conclusions: Psychological distress was found to be low among the pregnant women in this study. Fear of being without help and fear of contacting the virus during the visit to the hospital during the Covid-19 pandemic were the likely reasons of the psychological distress in the pregnant women. Keywords: Coping; pregnancy;Psychological distress.